Handgrip strength in practitioners of different sports and ages (Research, Society and Development, 2023)
The objective of this study was to identify the possible variations of handgrip in practitioners of different sports and with different age groups, since the aging process is something natural and irreversible, and handgrip is one of the safety indicators in this process, giving stability, confidence and functionality to the individual. The loss of lean mass, known as sarcopenia, is directly linked to the lack of stimuli for muscle fibers, so the present study investigated 90 individuals with different age groups, divided into groups every 10 years and regular practitioners of different sports modalities, who read and signed the TCLE, approved by the CEP of the University of Paso Fundo - UPF. The individuals performed the handgrip test with the manual dynamometer, where the participant was seated with the feet supported and the elbow flexed at 90º, performing the test in two attempts, with the highest performance being marked, both on the dominant and non-dominant sides. It was possible to perceive that the age group from 18 to 29 years old, presented the highest handgrip strength, and this was gradually reduced throughout life and the Judo modality, presented the highest rates among the evaluated modalities.